Methods of Teaching Old and Modern Arabic Language/طرائق تدريس اللغة العربية القديمة و الحديثة - Baiq Tuhfatul Unsy (Nurul Jadid University, 2018)
The aim of this research is to learn the methods of teaching the Arabic language from time to time. It means old methods and modern methods. Each has characteristics that contradict one another. These differences are in terms of purpose, entry and evaluation. And teaching Arabic to non-Arabic speakers. Therefore, the teacher's knowledge of the modern and old teaching methods and his ability to use them helps him to know the teaching conditions that surround the educational situation. The education process becomes attractive and enjoyable for the learner and is relevant to his daily life, needs, tendencies, desires and future aspirations, so that the teaching of Arabic as a second language will be successful and a means of fully understanding Islam.هدف هذا البحث إلى معرفة طرائق تدريس اللغة العربية المختلفة من قديم الزمان إلى وقتنا الحاضر. ويعني بها الطرائق القديمة والطرائق الحديثة. ولكل منهما خصائص يخالف يعضها عن غيرها. وتلك الاختلافات تكون من حيث الغرض والمدخل والتقويم. وتعليم اللغة العربية للناطقين بغيرها. لذا، فإن معرفة المدرس بطرائق التدريس الحديثة والقديمة وقدرته على استعمالها تساعده في معرفة الظروف التدريسية التي تحيط بالموقف التعليمي. إذ تصبح عملية التعليم محببة وممتعة للمتعلم ووثيقة الصلة بحياته اليومية واحتياجاته وميوله ورغباته وتطلعاته المستقبلية، حتى ينجح تعليم اللغة العربية كلغة ثانية ووسيلة لفهم الإسلام بشكل كامل شامل.